Comparative chromosome mapping of repetitive sequences. Implications for genomic evolution in the fish, Hoplias malabaricus - Cioffi, Marcelo B.; Martins, Cesar [UNESP]; Bertollo, Luiz A. C. (Biomed Central Ltd., 2009)
Background: Seven karyomorphs of the fish, Hoplias malabaricus (A-G) were previously included in two major groups, Group I (A, B, C, D) and Group II (E, F, G), based on their similar karyotype structure. In this paper, karyomorphs from Group I were analyzed by means of distinct chromosomal markers, including silver-stained nucleolar organizer regions (Ag-NORs) and chromosomal location of repetitive sequences (18S and 5S rDNA, and satellite 5SHindIII-DNA), through fluorescence in situ hybridization (FISH), in order to evaluate the evolutionary relationships among them.Results: The results showed that several chromosomal markers had conserved location in the four karyomorphs. In addition, some other markers were only conserved in corresponding chromosomes of karyomorphs A-B and C-D. These data therefore reinforced and confirmed the proposed grouping of karyomorphs A-D in Group I and highlight a closer relationship between karyomorphs A-B and C-D. Moreover, the mapping pattern of some markers on some autosomes and on the chromosomes of the XY and X(1)X(2)Y systems provided new evidence concerning the possible origin of the sex chromosomes.Conclusion: The in situ investigation of repetitive DNA sequences adds new informative characters useful in comparative genomics at chromosomal level and provides insights into the evolutionary relationships among Hoplias malabaricus karyomorphs.